Abstract ID: 28 Evaluation of silicon and diamond based microdosimetry for boron neutron capture therapy quality assurance. (October 2017) - Guatelli, Susanna; Vohradsky, James; Davis, Jeremy; Tran, Linh T.; Rosenfeld, Anatoly
Abstract : The shift from reactor to accelerator based neutron production has created a renewed interested in Boron Neutron Capture Therapy (BNCT). BNCT is reliant upon the favourable uptake of boron 10 by tumour cells along with the interaction with neutrons to produce high LET fragments (He and Li nuclei) that deposit energy locally within the tumour site. As with any radiation based treatment, Quality Assurance (QA) is crucial. This study extends previous work regarding the application of solid state microdosimetry in the field of BNCT by means of a dedicated Monte Carlo simulation[1] . Geant4 was used to model and optimise the design of silicon on insulator and diamond based microdosimeters[2, 3] . Detector optimisation in this context pertains to the geometry and materials (i.e., sensitive volume size and probability of neutron activation) to be used in the fabrication of detectors. The study has shown conclusively that whilst the materials currently used in the fabrication of silicon and diamond based microdosimeters are appropriate, there are changes with respect to the sensitive volume thickness that must be addressed. Lastly, the applicability of previously determined correction factors[4] to match the energy deposition response of charged particles within silicon/diamond to water was evaluated within the context of BNCT. Full results and analysis will be presented.